Antidote-induced armchair graphene nanoribbon based resonant tunneling diodes. (23rd June 2021) - Hossain, Tanvir; Istiaque Rahaman, Md; Alam, Mahbub
Abstract: Resonant tunneling phenomena are explored using armchair graphene nanoribbon (AGNR), which eliminates the lattice mismatch and electron mobility degradation problems of conventional heterostructure resonant tunneling diodes (RTDs). Eight antidote topologies are proposed in this paper. These antidote topologies significantly increase or decrease the band gap of AGNR. Both double barrier quantum well and single barrier quantum well structures have been achieved by putting the antidote-induced AGNRs and pristine AGNRs. A numerical approach with a tight binding model and non-equilibrium Green's function formalism has been used to simulate the quantum phenomena of the device. Current–voltage characteristics of these proposed RTDs show a high peak to valley ratio and low power dissipation with respect to different antidote topologies. Channel length variation effects are investigated in the proposed RTDs, and it is found that the peak to valley ratio, valley current, valley voltage, and power dissipation can be improved by tuning the channel length. These graphene-based RTDs are easy to fabricate and offer more flexibility in terms of peak to valley ratio, valley current, valley voltage, and power dissipation.